Looking at Social Assistance: Is It Effective in Strengthening the Economy in East Java? - Ayesha Tantriana; Suryo Adi Rakhmawan (East Java Economic Journal, 2024)
During the economic uncertainty, social assistance has become the core of COVID-19 and unstability of global geopolitics mitigation strategies. Both national and regional governments in Indonesia have expanded the coverage of social assistance programs during the pandemic. The increase in poverty rate in East Java highlights the needs to evaluate the effectiveness of the programs. This paper aims to estimate the causal effect of receiving social assistance on household economic behavior. Using the National Social and Economic Survey (SUSENAS), a panel survey in 2022-2023, this paper implements the analysis of multivariate of variance (MANOVA) and Difference-in-Difference (DiD) method. The results show a significant difference in household consumption and food insecurity among those who received the assistances. Notable impacts were found among rural and women-headed households. This study also emphasizes the variation in the effectiveness of the programs given by national and regional governments. In line with previous studies, social assistance had negative effect on employment in terms of the recovery of informal sectors. To build economic resilience in East Java, this paper recommends a segmentation and better-targeting of social assistance.